About effect of chloride- and nitro-bearing polymers interaction in adhesion compositions - S. V. Kotova; L. R. Lusova; V. A. Glagolev; S. G. Karpova; N. M. Livanova (Тонкие химические технологии)
The opportunity of modification of adhesives based on nitrile-butadiene rubber with chlorinated PVC is shown